Female Education, Poverty, and Household Factors in Reducing Stunting in Indonesia - Anita Kartika Putri; Ida Budiarty (International Journal of Economics and Management Sciences, 2026)
Stunting remains a persistent nutritional challenge that threatens human capital development in Indonesia. This study examines the effects of exclusive breastfeeding, female education, sanitation, access to safe drinking water, inadequate food consumption, and poverty on stunting prevalence across 34 provinces in Indonesia during 2017–2024. The study employs a random-effects Panel EGLS estimator with Panel Corrected Standard Errors (PCSE) to address heteroskedasticity and cross-sectional dependence in provincial panel data. The findings reveal that exclusive breastfeeding, female education, and adequate sanitation significantly reduce stunting prevalence, while poverty significantly increases it. Interestingly, inadequate food consumption is negatively associated with stunting prevalence, potentially reflecting the contribution of government nutritional assistance and social protection programs. In contrast, access to safe drinking water does not show a statistically significant effect. Among the explanatory variables, female education is strongly associated with reductions in stunting. These findings highlight the importance of strengthening women’s education, improving sanitation quality, and expanding poverty-alleviation and nutrition-sensitive interventions to accelerate reductions in stunting and support the achievement of Sustainable Development Goal 2 in Indonesia.